Present Status and Future Perspectives of the NEXT Experiment. (18th March 2014) - Gómez Cadenas, J. J.; Álvarez, V.; Borges, F. I. G.; Cárcel, S.; Castel, J.; Cebrián, S.; Cervera, A.; Conde, C. A. N.; Dafni, T.; Dias, T. H. V. T.; Díaz, J.; Egorov, M.; et al.
Abstract : NEXT is an experiment dedicated to neutrinoless double beta decay searches in xenon. The detector is a TPC, holding 100 kg of high-pressure xenon enriched in the 136 Xe isotope. It is under construction in the Laboratorio Subterráneo de Canfranc in Spain, and it will begin operations in 2015. The NEXT detector concept provides an energy resolutionbetter than 1% FWHM and a topological signal that can be used to reduce the background. Furthermore, the NEXT technology can be extrapolated to a 1 ton-scale experiment.